Cytotoxic Effect of Andrographis paniculata Associated with 2-Aminoethyl Dihydrogen Phosphate in Triple-Negative Breast Cells - Rosa Andrea Nogueira Laiso; Julia Carolina Ferreira; Rose Eli Grassi Rici; Laertty Garcia de Sousa Cabral; Durvanei Augusto Maria (Current Issues in Molecular Biology, 2024)
Cancer stands out as a major global public health concern and a significant impediment to increasing life expectancy worldwide. Natural bioactives derived from plants are renowned for their efficacy in treating various types of cancer. Andrographis paniculata (Burm.f.) is a well-known plant traditionally employed in diverse medical systems across the globe. The 2-AEH2P monophosphoester, a molecule intricately involved in phospholipid turnover, demonstrates antiproliferative effects across a broad spectrum of cancer types. This study aims to assess the antitumor, antiproliferative, and pharmacological effects of andrographolide at different concentrations, both individually and in conjunction with 2-aminoethyl dihydrogen phosphate. The cytotoxicity of the treatments was evaluated using the colorimetric MTT method, cell cycle phases, mitochondrial electrical potential, and markers expression via flow cytometry, while the pharmacological effects were assessed using SynergyFinder software 3.0. Treatments with A. paniculata, isolated at concentrations of 10%, 30%, and 50% of andrographolide, induced cell death in tumor cells, resulting in a reduction in mitochondrial electrical potential and alterations in cell cycle phases, particularly a decrease in the population of MDA MB-231 cells in the G0/G1 phase. The combination treatments exhibited significant cytotoxicity toward tumor cells, with minimal toxicity observed in normal fibroblast cells FN1. This led to a reduction in mitochondrial electrical potential and cell cycle arrest in the S phase for MDA MB-231 cells. Across all concentrations, the combined treatments demonstrated a synergistic pharmacological effect, underscoring the efficacy of the association. There was a change in the markers involved in cell death, such as p53, caspase 3, Bcl-2, and cytochrome c, suggesting the induction of regulated cell death. Markers associated with progression and proliferation, such as cyclin D1 and p21, corroborate the findings for cytotoxicity and cell cycle arrest.